Arus Baru Politik Islam: Pluralisme, Kontestasi, dan Demokratisasi - Muhammad Adib; Nur Qomari (Fakultas Syariah - IAI Al-Qolam Malang, 2018)
The recently political contestations in the Muslim world confirmed a new wave of Islamic politics. The political dynamics that have revolved so quickly and surprisingly, especially in non-Arab countries, are evidence that questioning the harmony between Islam and democracy, pluralism and human rights is no longer relevant. Even though it is not monolithic and is still in the “process of becoming”, the political dynamics that are revolving in a number of Muslim-majority countries actually lead to the same goal, namely the realization of a democratic and civilized politics. Keywords: Political Contestation, Democratization, Process of Becoming